2021
DOI: 10.1111/aji.13475
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocytes and preeclampsia: The potential role of T‐cell subsets and related MicroRNAs in the pathogenesis of preeclampsia

Abstract: Innate and adaptive immune systems have a crucial role in initiating and progressing some pregnancy disorders such as preeclampsia (PE), which is one of the pregnancy‐specific disorders that could result in neonatal and maternal morbidity and mortality. The dysregulation of the spiral artery and inadequate trophoblast invasion lead to PE symptoms through producing various inflammatory cytokines and anti‐angiogenic factors from the placenta. T lymphocytes play a special role in the epithelium and stroma of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 142 publications
(233 reference statements)
1
12
0
Order By: Relevance
“…In particular, T reg cells exert immune tolerance functions by mechanisms including antigen presentation, secretion of inhibitory cytokines and cytolysis of target cells 152,153 . Abnormal release of T reg cell factors, including cytokines and microRNA, is found in pre-eclampsia 154 . Epidemiological studies support experimental data reporting that the maternal immune response to paternally derived antigens on the trophoblast 155 is decreased by previous exposure to seminal fluid 156 : a higher incidence of pre-eclampsia is found in primiparity, pregnancies in which the paternity has changed, pregnancies after a prolonged inter-pregnancy interval (>10 years), pregnancies conceived soon after first coitus, and pregnancies conceived with the use of donor egg 157 and sperm 90 .…”
Section: Primermentioning
confidence: 99%
“…In particular, T reg cells exert immune tolerance functions by mechanisms including antigen presentation, secretion of inhibitory cytokines and cytolysis of target cells 152,153 . Abnormal release of T reg cell factors, including cytokines and microRNA, is found in pre-eclampsia 154 . Epidemiological studies support experimental data reporting that the maternal immune response to paternally derived antigens on the trophoblast 155 is decreased by previous exposure to seminal fluid 156 : a higher incidence of pre-eclampsia is found in primiparity, pregnancies in which the paternity has changed, pregnancies after a prolonged inter-pregnancy interval (>10 years), pregnancies conceived soon after first coitus, and pregnancies conceived with the use of donor egg 157 and sperm 90 .…”
Section: Primermentioning
confidence: 99%
“…Human CD4+ T cells can be classified into Th1, Th2, regulatory T (Treg), and Th17 cells based on their pattern of cytokine production, and they display different biological functions [ 30 , 31 ]. Research has proposed that successful pregnancy is a Th2 type phenomenon, and Th1 type reactivity is harmful to pregnancy [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the balance between Th1/Th2 functions in peripheral blood and decidua changes toward a Th1-dominated inflammatory phenotype in preeclamptic patients ( 56 , 57 ). Th1 induced chronic inflammatory reactions in the fetal- maternal interface, placental damage and endothelial dysfunction by secreting the amounts of TNF-α, IFN-γ, IL- 1β, and IL- 12 ( 58 ).Preeclamptic symptoms such as elevated blood pressure, proteinuria and renal function abnormalities occur in pregnant mice after Th1 cell importation ( 59 ). A growing number of studies have found that disruption of Treg/Th17 balance can lead to the development of preeclampsia and that the balance between Treg and Th17 is essential for the prevention of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%